Stickers for Nails: The Ongoing Transformation of Roles, Rites, and Symbols in Japanese Funerals - Rowe, Mark Michael (Japanese journal of religious studies, 2000)
This article traces the effects of modern commercial ritual spaces and new crematoriums on the meaning and structure of contemporary Japanese funerals. The widening physical separation between the mourning family and the corpse throughout the death process parallels an increase in the ritual authority of the professional funeral industry, which has led to several notable variations in funeral styles. Of particular note is a changing attitude towards the corpse that emphasizes the physical (consumer) comfort and individual needs of the deceased over the pacification of the spirit.